Long-term bond strength of a self-adhesive resin cement to intraradicular dentin pretreated with chlorhexidine and ethanol - Mariah Carvalho Guimarães dos SANTOS; Flávia Lucisano Botelho AMARAL; Cecília Pedroso TURSSI; Roberta Tarkany BASTING; Fabiana Mantovani Gomes FRANÇA (Universidade Estadual Paulista, 2017)
Abstract Introduction Self-adhesive resin cements do not require prior preparation of the tooth surface, therefore dentin pretreatments may influence long-term bond strength. Objective To evaluate the influence of 100% ethanol (ET) and 2% chlorhexidine (CL) treatment of intraradicular dentin on the long-term bond strength (BS) of a self-adhesive resin cement (SRC). Material and method 80 bovine roots were restored with fiber posts and SRC (U200 3M/ESPE) and distributed into 4 groups according to dentin treatment: Group 1 - without treatment; Group 2 - 2% CL for 1 minute; Group 3 - 100% ET for 1 minute; Group 4 - 2% CL, followed by 100% ET. The samples were cross-sectioned to obtain two sections (0.7 mm) thick for each root third: coronal, middle and apical. The immediate push-out test was carried out after 48 hours, and the long-term push-out test, after 180 days. Result The three-way ANOVA test for randomized blocks showed no difference between the BS values at 48 hours and 80 days, irrespective of the treatment and the third (p>0.05). The interaction of the treatment/third pairing was significant (p = 0.041) since the treatment with CL promoted lower BS in the coronal third, while treatment with ET promoted better BS in the apical third. Conclusion Treatment with CL and ET, separately or combined, promoted no differences between the BS values of the SRC to root dentin over time.